The material school culture as a source of research in educational practices in Sao Joao del-Rei, Minas Gerais, Brazil (1938-1944) - Laerthe de Moraes Abreu Junior; Paula Cristina David Guimarães (Universidade Estadual Paulista Júlio de Mesquita Filho, 2011)
This work within the domain of Education history research, more specifically in the culture of school material's research. It investigates the teaching practices in the second school group created in the town of Sao Joao del-Rei from 1938 to 1944 through its files, where part of the materials used at that time are kept, being most of them official documents. The two main documents analyzed were Livro de atas e termos de promoção and Livros de matricula. These primary research sources were not analyzed in isolation, the data from these materials were crossed, which allowed a greater understanding of the school practices undertaken by the school group at the time. The analysis of the materials was carried out considering the historical moment in which they were produced, the "New State"